Ocorrência de Pseudomerulius curtisii, Gelatoporia subvermispora e Sarcoporia polyspora no sul do Brasil - Baldoni, Daiana Bortoluzzi (2012)
The Pampa is the newest Brazilian biomes. It is one of the lest studied and the one of the most economically exploited. Among these forms of exploitation, there is the cultivation of great dominated grassy fields with exotic forest species. Researches involving animal and plant species have revealed great biodiversity, however, they are still rare for microorganisms. The aim of the study was to collect, to isolate and to analyze morphologically and molecularly three wood-decaying fungi growing on Pinus sp. in Pampa biome: Pseudomerulius curtisii (Berk.) Redhead & Ginns, Gelatoporia subvermispora (Pilat) Niemelä and Sarcoporia polyspora P. Karsten. It was conducted the morphological characterization and the sequencing of ITS1-5.8S-ITS2 of species allowing their identification and phylogenetic comparisons with the literature. P. curtisii calls attention to the rarity and beauty of the basidiome and morphological similarities with specimens of the Northern Hemisphere and Oceania, but with a genetic distance, and may show the geographic isolation and the new taxon to be described. G. subvermispora, widely studied by the high biotechnology and industrial potential. It has high similarity with morphogenetic U.S. specimens, but with genetic divergence of Eurasian specimens. S. polyspora shows high morphological similarity with the specimens of the northern hemisphere, but there is a lack of sequences available for phylogenetic comparison. These species were registered for the first time in South America. P. curtisii, G. subvermispora and S. polyspora, fungi Basidiomycota show high potential for nutrient cycling and soil formation by the capacity or lignin and cellulose degradation.